CHANGES IN CONSUMER PERCEPTIONS TOWARDS GLOBAL BRANDS POST GLOBALIZATION IN INDIAN TELEVISION INDUSTRY - Jhaveri, Sagar (2007)
The aim of the study is to understand the reasons of brand shifting in the Indian consumers. The research aims to find out the why post globalization the preferences of the Indian consumer especially in the Television Industry have changed towards global brands and why the local brands are loosing market share and brand awareness. The main aim was to understand the unique behaviour of different consumers towards global and local brands. Another objective was to find whether the factor like Country-of-origin had any effect on the perceptions of the consumer while purchasing a brand. Finally the research ended by asking the respondents their suggestions for how local brands could be more effective and competitive when competing with global players.